Juggling online gigs with offline jobs: How local labour markets are driving the growth in internet and platform work - Wouter Zwysen; Agnieszka Piasna (European Trade Union Institute (ETUI), 2023)
Online labour platforms are redefining the world of work, but little is known even now about the drivers of worker engagement in this type of activity. Earlier studies focused on individual preferences and job characteristics such as flexibility or low entry barriers, but the relative role of such pull factors is limited given widespread worker discontent and generally precarious and unstable conditions, in many respects similar to the low-wage and informal sector. This working paper expands current frameworks by considering the role of the local economic and employment context in explaining the prevalence of internet and platform work. Our analysis uses the ETUI Internet and Platform Work Survey carried out in Spring and Autumn 2021 with representative cross-national data covering 14 European countries. The results show a higher likelihood of engaging in online work in regions with worse offline opportunities - that is, fewer jobs and of lower quality overall. As internet work is often a secondary source of income, this is likely to reflect a greater juggling of offline and online jobs, driven by increasing economic and job insecurity.
Keywords: 330; gig economy; job quality; local labour market; online labour platforms